ANALYTICAL STUDY OF FARMER SUICIDE IN INDIAN AGRICULTURE SECTOR - JASBIR SINGH (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, ECONOMICS & MANAGEMENT, 2013)
Indian farmers are in problem due to indebtness in India. Eleven crore farmer families are in problem. On an average a farmer has 80000 Rs per head debt in India (NSSO 2006). India is an agrarian country with around 60% of its people directly or indirectly depends upon agriculture. Agriculture in India is often attributed as gambling with monsoons because of its almost exclusive dependency on precipitation from monsoons. The failure of these monsoons leading to a series of droughts, lack of better prices, exploitation by Middlemen, all of which have led to a series of suicides committed by farmers across India. Since 1995, more than 253,000 farmers have been reported to have committed suicides in India, making this the largest wave of suicides in the world. On an average 45 farmers commit suicide each day in India and in Vidharb a farmer commit suicide each every five hour. Innovative remedies have to be thought of which are to be implemented with sincerity by the Government and the implementing agencies, along with putting in place ways to rehabilitate the affected farmers. An attempt has been made in this article to address the issue of farmer’s plight leading to suicide and measures to address the issue have been suggested.